Gene therapy with IL-12 induced enhanced anti-tumor activity in fibrosarcoma mouse model. (16th November 2016) - Razi Soofiyani, Saiedeh; Kazemi, Tohid; Lotfipour, Farzaneh; Mohammad hosseini, Akbar; Shanehbandi, Dariush; Hallaj-Nezhadi, Somayeh; Baradaran, Behzad
Abstract: Context Immunotherapy is among the most promising modalities for treatment of cancer. Recently, interleukin 12 (IL-12) has been used as an immunotherapeutic agent in cancer gene therapy. IL-12 can activate dendritic cells (DCs) and boost anti-tumor immune responses.Objective In the current study, we have investigated if IL-12 gene therapy can lead to the regression of tumor mass in a mouse model of fibrosarcoma.Material and methods To investigate the therapeutic efficacy of IL-12, WEHI-164 tumor cells were transfected with murine-IL12 plasmids using Lipofectamine. Enzyme linked immunosorbent assay (ELISA) was used to confirm IL-12 expression in transfected cells. The fibrosarcoma mouse model was established by subcutaneous injection of transfected cells to Balb/C mice. Mice were sacrificed and the tumors were extracted. Tumor sizes were measured by caliper. The expression of IL-12 and IFN-γ was studied with real-time PCR and western blotting. The expression of Ki-67(a tumor proliferation marker) in tumor mass was studied by immunohistochemistry staining.Results and discussion The group treated with IL-12 showed a significant decrease in tumor mass volume ( P : 0.000). The results of real-time PCR and western blotting showed that IL-12 and IFN-γ expression increased in the group treated with IL-12 (relative expression of IL-12: 1.9 and relative expression of IFN-γ: 1.766). Immunohistochemistry staining showed that Ki-67 expression was reduced in the group treated with IL-12.Conclusion IL-12 gene therapy successfully led to regress of tumor mass in the fibrosarcoma mouse model. This may serve as a candidate therapeutic approach for treatment of cancer.